Managing the return of foreign terrorist fighters in Southeast Asia: complexities and challenges - El-Muhammady, Ahmad (2021)
The presentation discusses Malaysia’s experience of managing the returning fighters and their families, the challenge we face and some recommendation. It covers six aspects: 1) The framework for understanding FTF phenomenon 2) Foreign Terrorist Fighters?. 3) The policy of repatriation. 4) Assessment, rehabilitation, and judicial process are the pillars of managing the returnees. 5) Challenges in managing returning fighters and their families faced by the authorities, and civil society sectors. 6) Some Recommendation